EVALUATION OF SOIL EMBANKMENT MASS MOVEMENT BY USING SUBDRAIN SYSTEM AND REINFORCEMENT BASED ON THE NUMERICAL SIMULATION OF SEMARANG-SOLO TOLL ROAD - Syahbudin Dayanun; Ahmad Rifa’i; Kabul Basah Suryolelono (Journal of the Civil Engineering Forum, 2014)
Semarang-Solo highway is a part of Trans Java Toll Road System, which in construction stage has soil embankment mass movement between Sta. 5+ 500, -5+800 part II Gedawang-Penggaron. In this case, research is conducted to again effective and efficient solution. The research object is soil embankment which moved on site. The research aim is to identify the cause of soil embankment mass movement, to know the effect of sub drain system to soil movement and also to provide alternative solution. Slope stability analysis was solved by Plaxis, based on topography, investigation data and field instrumentation after gain the validation result with accuracy of soil movement on horizontal direction of the slope, continued by simulation with variants model which affected by strength, loading combination (traffic load), water level (dry and raining season), sub drain system and earthquake. Horizontal movement result of simulation can be seen in location of inclinometer 4.The research result shown that soil movement pattern which strengthened with bored pile is sliding combination type of translation and rotation. The strengthened soil embankment mass with bored pile apparently still has movement as 0,246 m with SF 1,448. Due to traffic load, horizontal movement is 0,322 m with SF 1,368 where water level located in 5,5 m at BM 10 and 3,5 m at BM 11 and sub drain is pointed in 4 m mean depth. When rainy season the horizontal movement increase 0,324 m with SF 1,321 while in dry season become 0,320 m with SF 1,479. When sub drain existing reduce in average 2,0 m so horizontal movement also decrease as 0,254 m with SF 1,465. Earthquake simulation shown maximum horizontal movement is 1,422 m with SF 1,193. As alternative to minimize horizontal movement which cause by earthquake can be solved by reduce embankment height from 25,72 m to 20,72 m, simulation result provide horizontal deformation as 0,703 m with SF 1,567. In hence the existence of sub drain construction able to reduce horizontal movement of soil embankment mass in which increase the safety factor, reduction of embankment height also show positive impact and significant to horizontal movement due to earthquake.Keyword : soil mass movement, Plaxis program, sub drain system